Kajian Struktur Rangka Batang Jembatan Wailola Besar Kabupaten Seram Bagian Timur - Laipeny, Fredrik Hendrik; Lewakabessy, Godfried; Roberth, Herry Henry (VISA: Journal of Vision and Ideas, 2024)
The Wailola Besar Bridge, which is located in Bula District, East Seram Regency, has a Warren truss type frame structure. However, unlike the truss used on other bridges, the truss on the Wailola Besar bridge has a larger size than the others. Because the span of the Wailola Besar bridge is 80 m, while the span of other bridges using the Warren truss type is a maximum of 60 m. The larger size than the other trusses makes the Wailola Besar bridge have a different truss from other trusses. The length of each horizontal bar is 6.65 m, while the maximum length for other bridges is 5 m. Then the purpose of this study is to determine whether the truss structure of the Wailola Besar bridge is capable of carrying the loads acting on the bridge, the method used is with the help of the SAP-2000 program to determine the truss forces then controlled with allowable voltage. In order to know whether the structure is able to withstand the forces acting. From the results of calculations with the help of SAP-2000 the rod forces acting on the largest truss structure are 11066.881 KN at constant loading and 12222.547 KN at temporary loading and the stress that occurs is 1742.82 Kg/〖cm〗^2. at constant loading and 1924.81 Kg/〖cm〗^2. The stress that occurs in the truss does not exceed the allowable stress.